Influence of geometrical parameters roller bearing cone on its service life - Маковкін, О.М. (Problems of Tribology, 2016)
Makovkin O.M. Influence of geometrical parameters roller bearing cone on its service life. The results of experimental studies of the effect of geometrical parameters of roller bearing bits to turn the roller as a result of wear. It is proved that the maximum service life of the bearing bits can be achieved by changing the length and diameter roller and roller treadmill. It was established that the reversal rollers least affected by the change in the diameter of the treadmill, two orders of magnitude greater impact changing the diameter of the roller, and a crucial role in increasing the length moto plays video. Keywords: bearing, roller reversal, roller length, roller track.